Democracy in the making : how activist groups form - Blee, Kathleen M. (New York ; Oxford : Oxford University Press, 2012)
Kathleen M. Blee provides an in-depth look at modern grassroots activism, and reveals its simultaneous power and fragility. In the process, she examines the struggle between democratic vision and strategic reality that shapes each organisation's trajectory and determines its ultimate success or failure.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on Apr. 26, 2012).
Keywords: Social movements -- Pennsylvania -- Pittsburgh -- History -- 21st century; Social change -- Pennsylvania -- Pittsburgh; Democracy -- Pennsylvania -- Pittsburgh